Academic Benefits from Parental Involvement are Stratified by Parental Socioeconomic Status: A Meta-analysis. (1st October 2020) - Tan, Cheng Yong; Lyu, Meiyan; Peng, Baiwen
SYNOPSIS: Objective . The present study critically evaluates the assumption that parental involvement benefits students' achievement regardless of their socioeconomic status (SES). Design . A meta-analysis of 98 studies published 2000–2017 examines if patterns of associations between 11 specific parental involvement variables and the academic achievement of K-12 students vary with parental SES as measured by educational level. Results . Results showed that (1) six specific aspects of parental involvement, namely parental academic expectations, parental support for child learning, parent-child discussion of school matters, parental participation in school governance and events, parent and child reading together, and parental emphasis on education, were positively associated with student achievement; (2) subtle forms of parental involvement were most strongly associated with student achievement, followed by home- and school-based involvement; (3) parental learning support at home, parental academic emphasis, and parent-teacher communication had stronger association with the achievement of students whose parents were more educated; (4) parent-teacher communication and parental academic emphasis for college-educated parents did not additionally benefit student achievement when compared to these involvement activities for parents with at most Grade-12 education; and (5) parental involvement was more strongly associated with the linguistic achievement of students with highly educated parents. Conclusions . These results provide evidence that some benefits of parental involvement are stratified by familial SES.